Quality management overview for the production of a tissue-engineered human skin substitute in Malaysia - Wan Tai Seet; Mohd Asyraf Mat Afandi; Mohamad Fikeri Ishak; Muhammad Najib Fathi Hassan; Nazeha Ahmat; Min Hwei Ng; Manira Maarof (Stem Cell Research & Therapy, 2023)
Abstract Treatments for skin injuries have recently advanced tremendously. Such treatments include allogeneic and xenogeneic transplants and skin substitutes such as tissue-engineered skin, cultured cells, and stem cells. The aim of this paper is to discuss the general overview of the quality assurance and quality control implemented in the manufacturing of cell and tissue product, with emphasis on our experience in the manufacturing of MyDerm®, an autologous bilayered human skin substitute. Manufacturing MyDerm® requires multiple high-risk open manipulation steps, such as tissue processing, cell culture expansion, and skin construct formation. To ensure the safety and efficacy of this product, the good manufacturing practice (GMP) facility should establish a well-designed quality assurance and quality control (QA/QC) programme. Standard operating procedures (SOP) should be implemented to ensure that the manufacturing process is consistent and performed in a controlled manner. All starting materials, including tissue samples, culture media, reagents, and consumables must be verified and tested to confirm their safety, potency, and sterility. The final products should also undergo a QC testing series to guarantee product safety, efficacy, and overall quality. The aseptic techniques of cleanroom operators and the environmental conditions of the facility are also important, as they directly influence the manufacturing of good-quality products. Hence, personnel training and environmental monitoring are necessary to maintain GMP compliance. Furthermore, risk management implementation is another important aspect of QA/QC, as it is used to identify and determine the risk level and to perform risk assessments when necessary. Moreover, procedures for non-conformance reporting should be established to identify, investigate, and correct deviations that occur during manufacturing. This paper provides insight and an overview of the QA/QC aspect during MyDerm® manufacturing in a GMP-compliant facility in the Centre for Tissue Engineering and Regenerative Medicine, Faculty of Medicine, Universiti Kebangsaan Malaysia.